Extracorporeal photopheresis for the treatment of severe, refractory steroid dependent pediatric Crohn's Disease. Issue 5 (30th May 2013) - Cheerva, Alexandra; Dillard, Robert; Bertolone, Salvatore
<x xml:space="preserve">Abstract</x> Crohn's disease is a chronic, inflammatory disease of the gastrointestinal tract, affecting both children and adults. Extracorporeal photopheresis (ECP) has been used in steroid dependent adults with moderate to severely active Crohn's disease, with response rates up to 50%, with up to 25% complete responses. A 12‐year‐old male patient had severe unremitting Crohn's disease for one year, despite treatment with anti‐inflammatory, immunosuppressive, and biologic agents. He failed elemental enteral nutrition and required total parenteral nutrition (TPN). A diverting colostomy for perforation was required. He required frequent hospitalizations and required homebound schooling. Endoscopy revealed severe inflammation and ulcerations of the entire colon. ECP was begun twice weekly for 4 weeks, then twice per week every 14 days for a total of 28 weeks. ECP was well tolerated and prednisone was gradually discontinued. He continued daily azathioprine and infliximab at 6 week intervals. TPN was weaned as enteral intake improved. Disease abatement allowed a return to school and normal activities. Endoscopy at completion of ECP course revealed normal upper tract, normal ano‐rectum, and decreased, although significant, colonic disease. This response has continued for at least 16 months since completion of ECP. We conclude that ECP is useful for pediatric patients with steroid dependent Crohn's disease and prospective evaluation is warranted. J. Clin. Apheresis 28:381–386, 2013. © 2013 Wiley Periodicals, Inc.